2015
DOI: 10.5688/ajpe7910151
|View full text |Cite
|
Sign up to set email alerts
|

Student-Valued Measurable Teaching Behaviors of Award-Winning Pharmacy Preceptors

Abstract: Objective. To identify specific preceptor teaching-coaching, role modeling, and facilitating behaviors valued by pharmacy students and to develop measures of those behaviors that can be used for an experiential education quality assurance program. Methods. Using a qualitative research approach, we conducted a thematic analysis of student comments about excellent preceptors to identify behaviors exhibited by those preceptors. Identified behaviors were sorted according to the preceptor's role as role model, teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
(36 reference statements)
1
21
0
Order By: Relevance
“…The creation of a fully online elective APPE rotation was a significant undertaking considering the ambitious schedule, staff requirements, and preceptor involvement required. Literature shows that pharmacy students greatly value APPE rotations to hone their clinical skills through real patient‐care activities 14‐16 . Given that typical direct patient care rotations were not possible, a virtual learning experience was designed that attempted to replicate the inpatient and outpatient learning environment as closely as possible in order to avoid interruption of clinical rotations and to ensure timely graduation.…”
Section: Discussionmentioning
confidence: 99%
“…The creation of a fully online elective APPE rotation was a significant undertaking considering the ambitious schedule, staff requirements, and preceptor involvement required. Literature shows that pharmacy students greatly value APPE rotations to hone their clinical skills through real patient‐care activities 14‐16 . Given that typical direct patient care rotations were not possible, a virtual learning experience was designed that attempted to replicate the inpatient and outpatient learning environment as closely as possible in order to avoid interruption of clinical rotations and to ensure timely graduation.…”
Section: Discussionmentioning
confidence: 99%
“…These are in line with role-modeling, teaching-coaching, and facilitating behaviors previously identified as being valued by students. 3 When looking at some of the attributes related to representing and advancing the profession in a positive manner (eg, service to the community and profession, leadership), fewer C/SOP reported that they assess these. This could in part be due to the difficulty in gathering this information from volunteer preceptors or perhaps C/SOP are assessing advancement of the profession in other ways not captured by this survey.…”
Section: Discussionmentioning
confidence: 99%
“…O'Sullivan and colleagues identified specific preceptor teaching-coaching, role modeling, and facilitating behaviors valued by pharmacy students and developed measures for those behaviors. 3 Assemi and colleagues interviewed personnel from 29 experiential education programs to identify common practices used for measuring the quality of their programs. Recommendations for the way in which preceptor assessment may be incorporated into an overall quality improvement process for experiential education were offered.…”
Section: Introductionmentioning
confidence: 99%
“…28 Variability in assessed performance can be frustrating for students, and not a benign phenomenon, because how preceptors distinguish between performance Values represent the categorization made by the greatest proportion of preceptor respondents perceived-to-be below expectations and performance that meets expectations has implications for students' ability to satisfactorily complete the clerkship, and to ultimately graduate. [29][30][31][32] Another important consideration is how pharmacy preceptors perceive the same performance, but for different levels of students. To our knowledge, this has not previously been investigated in health professional training, although in one study, medical student supervisors were interviewed to elicit what teaching strategies they employ to teach different levels of learners.…”
Section: Discussionmentioning
confidence: 99%